A Framework for Evaluating Alternate Institutional Arrangements for Fiscal Equalization Transfers - Shah, Anwar (World Bank, Washington, DC, 2012)
Fiscal equalization programs are fairly common features of intergovernmental fiscal relations in industrial countries. Some developing countries have also recently introduced these programs and still others are contemplating such programs. Institutional arrangements for fiscal equalization vary across countries with wide variations in the form and membership of the relevant decisionmaking bodies. This paper provides a simple neo-institutional economics framework for assessing alternative institutional arrangements for their impacts on simplicity, transparency, and objectivity of the equalization program, as well as transaction costs for various parties involved. Comparing institutional arrangements across different countries is a daunting task. The success of these arrangements depends on a multitude of factors. The success of governance structures for fiscal matters may depend not only on the incentives regime associated with their inner structures but also their interactions with other formal and informal institutions in the country. This paper presents a simple framework to understand these incentives and interactions and draw implications for their impacts on transactions costs for the society as a whole and achievement of societal objectives. An application of these concepts to the specific case of institutional arrangements for fiscal equalization transfers are carried out and the predictions based on the theory are compared with observed experiences in major federal countries. The paper demonstrates that the simple new institutional framework presented here has a significant power for predicting potential impacts. The paper concludes, both in theory and practice, that the case for independent grants commission to enhance the transparency, equity, and accountability of the intergovernmental finance system is vastly exaggerated.